Geological controls and exploration strategies for sandstone-type uranium ores: comparison of Indian deposits with those across the globe - Sharma, Shreya; Bharti, Rishikesh (Geologos, 2025)
The rising global energy demand has driven researchers to locate new uranium deposits, with sandstone types contributing nearly 40 per cent of uranium production. The present review provides a comprehensive understanding of the genesis and classification and mentions some global examples of sandstone-type uranium deposits, the focus being on the geological settings of each type. Understanding these factors helps locate similar deposits, especially in North-East India, where research is limited. There, uranium enrichment is controlled by numerous factors such as source rocks, sedimentary structures, permeability barriers, reductants and cap rocks. The present study underscores the need for integrated methods for exploration of sandstone-type deposits where remote sensing can be combined with geophysical and geochemical techniques.